Relationship of Internalized Transnegativity and Protective Factors With Depression, Anxiety, Non-suicidal Self-Injury and Suicidal Tendency in Trans Populations: A Systematic Review - Inderbinen, Marc; Schaefer, Kristin; Schneeberger, Andres; Gaab, Jens; Garcia Nuñez, David (Frontiers in Psychiatry, 2021)
Discrimination heavily impacts the lives of trans populations and causes adverse mental health outcomes. As stated by the Gender Minority Stress Model self-stigmatization could play an important role in this. The aim of this systematic review is to investigate whether there is a positive association between self-stigmatization and mental health and to identify factors that mediate this. Studies which quantitatively investigated the association between internalized transnegativity and one of the outcomes: depression, anxiety, non-suicidal self-injury, suicidal tendency, in trans populations were included. Comprehensive search of 5 large databases in June 2020 and the following screening and selection procedure, performed by two researchers separately, identified 13 studies which met criteria. The relationship to be studied was reported with correlation and/or mediation analysis of cross-sectional data. IT was directly positively associated with depression, anxiety and suicidal tendency in most of the reviewed studies. Data indicates links between self-stigmatization and other general mental health stressors such as rumination and thwarted belongingness. Community connectedness showed to be the strongest protective factor for mental health impairments. These results should be considered in transition counselling. More research is needed to better understand the underlying mechanisms of the GMSM and to address unsolved operationalization and measurement issues.